CREATIVE LEARNING PROCESS FOR TEACHERS ISLAMIC RELIGIOUS EDUCATION - Nadiva, Dewinta Nisa (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
In this paper discusses creative teachers in learning. Where we already know today about the many traits of each of the various learners. These properties besides positive are also negative. One negative for example the tendency to want to play, having fun in any form until lazy nugas, learning and others that cause knowledge and value to be lacking. Certainly, in this case if not islamic education teachers who have lead actors besides parents need new things or make them students who initially do not like to be like. The method used in this study is library reseach with primary and secondary data sources. Data collection techniques in this literature research include from books and journals with technical content analysis. The result of this paper is that creative teachers are intelligent teachers in practicing learning that makes students understand and enjoy learning. Creative teachers here are teachers who understand the right ways of teaching, models and strategies. The learning model is generally divided into contextual and conventional. In PAI learning if observed there are only a few models that can be applied including: investigation, discovery learning, problem based learning, problem solving, mind mapping, discussion method and learning together method. But before dissing the model used above, first a teacher must identify the behavior and character of students, approach, choose methods and create achievement targets in accordance with KI, KD and Indicators.